Mechanical tensile behaviour of cement paste/aggregate bond exposed to leaching. (10th March 2023) - Gîrboveanu, Andrei; Jebli, Mouad; Jamin, Frédéric; Huon, Vincent; Bonnet, Laurent; Georgescu, Dan; Saïd El Youssoufi, Moulay
Highlights: An experimental study concerns ITZ and the cement paste/aggregate bond. The cement paste and the bond are exposed to leaching. The impact of ITZ on the mechanical properties of the bond is evaluated. A microscopic study of ITZ accompanies observations on leaching. Effects of leaching kinetics, chemical dissolution and cracking are discussed. Abstract: An experimental program is oriented to the mechanical behaviour of the Interfacial Transition Zone (ITZ) exposed to leaching, for a single mix. Leaching kinetics of the degraded depth, measured through grey level on cross sections, reveals a maximum gap of 10 % between ITZ and bulk cement paste. ITZ, with a main thickness of 15 µm suffers a significant decalcification, which is reflected on the mechanical properties of the bond. Grey level, Calcium/Silicon (Ca/Si) molar ratio and Young's modulus in the degraded zone present similar evolution. Effect of ITZ causing cracking and then debonding is noticed, through chemical analysis, image observation and mechanical tests.